On the vowels of Imilike Dialect of the Igbo Language (2015)
This is a study of the vowels of Imilike dialect, a variety of Northern Igbo dialect. Its specific objectives include identifying the vowels of the dialect, determine their phonemic status, distributional pattern and phonotactic constraints and as well compare them with those displayed by the standard Igbo. Data for the study were collected using unstructured interview and observation. Data were analysed in the framework of generative phonology. Minimal pair test was conducted to identify the vowels of the dialect. The study reveals that the dialect displays eleven vowels including the open mid front unrounded vowel /£/ and the central vowels, [a] and [a]. AH except the central vowels are phonemic in the dialect. The central vowels are in free variation with other vowels in the dialect. AH the vowels occur in word initial, word medial and word final positions except the central vowels which do not occur in word initial position. The study also attests to the strict operation of vowel harmony in the dialect as in other Northern Igbo dialects. The study concludes that Imilike dialect displays more vowels than the standard Igbo.